Hubungan antara Parent Attachment dan Kompetensi Sosial pada Remaja Tengah di Sumatera Barat - widya febrina; Gumi Langerya Rizal (UNS Press, 2021)
Social competence is an individual’s skill or capacity that relates to other people and participates in a fun social context. One of the influences of social competence is the attachment between parents and children. Teens who have high attachment will have high social competence and vice versa. The purpose of this research is to see the relationship between attachment and social competence of adolescents in West Sumatra. Participants in this study were 150 adolescents aged 15-17 years. The technique used in this research is random sampling. The analytical method used is the person product moment correlation test with the help of SPSS 20.0 for windows. The results showed that the sign value was 0.00 (p